Africa and the Fathers: The relevance of early Hellenistic Christian theology for modern Africa - Bediako, Kwame (Jesus in Africa: The Christian gospel in African history and experience, 2000)
The phase of Christian history offering the most instructive parallels to the modern African context is the beginning of Hellenistic Christianity in the early Roman Empire. With Christianity virtually transposed from its original Jewish matrix and fast becoming a predominantly Gentile phenomenon, there emerged from the circles of Gentile Christian thought a significant body of Christian literature, in which the problem of Christian identity and the nature of continuity with the pre-Christian tradition began to be faced in earnest. Traditionally, early Christian writers have been studied largely for their contribution or otherwise to the development of Christian doctrine. Their careers...
paid